The Role of Financial Knowledge and Inclusion in MSME Behavior in Bangkalan - Adityani Nur Witasari; Helmi Buyung Aulia Safrizal; Kurniawan, Moh. Zaki (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This research examines the impact of financial knowledge and financial inclusion on the financial behavior of MSME actors in Bangkalan Regency. Using a quantitative approach, the study analyzes data from 80 MSME entrepreneurs selected through purposive sampling. The primary data was collected via structured questionnaires and analyzed using multiple regression techniques. The findings reveal that both financial knowledge and financial inclusion significantly influence the financial behavior of MSMEs in the region. This study contributes to the literature by addressing the gap in research on financial behavior among MSMEs in developing regions, particularly in Bangkalan. It combines financial knowledge and financial inclusion to provide a comprehensive understanding of financial behavior in this context. The study extends the behavioral finance framework and offers practical insights for policymakers and financial service providers to design inclusive financial policies and educational programs aimed at improving MSME financial practices. Theoretically, it enhances the understanding of financial behavior in rural MSME contexts, while practically calling for integrated policies that combine financial education with better access to financial services.